2010
DOI: 10.1002/ajh.21886
|View full text |Cite
|
Sign up to set email alerts
|

Current status of pediatric umbilical cord blood transplantation in Korea: A multicenter retrospective analysis of 236 cases

Abstract: We report the outcome of 236 pediatric umbilical cord blood transplantations (UCBT) performed in Korea. Given that the sources of the grafts were mostly unrelated donors (n 5 226; 95.8%), only the results of unrelated UCBT were included for all statistics. The most frequent primary disease was acute leukemia (n 5 167). In total, 91.7% of recipients were seropositive for cytomegalovirus (CMV). The median doses of nucleated cells and CD341 cells were 4.84 3 10 7 /kg and 2.00 3 10 5 /kg, respectively. The median … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 27 publications
3
15
0
Order By: Relevance
“…These findings suggest that severe CMV infection and possibly EBV infection might play a role in the progression of leukemia and might be a useful indicator of worsening the clinical course of the disease. Similar findings were reported by Yoo and his colleagues on Korean pediatric umbilical cord blood transplant patients where the presence of CMV disease was among factors that adversely affected the survival rates of all patients [34]. …”
Section: Discussionsupporting
confidence: 87%
“…These findings suggest that severe CMV infection and possibly EBV infection might play a role in the progression of leukemia and might be a useful indicator of worsening the clinical course of the disease. Similar findings were reported by Yoo and his colleagues on Korean pediatric umbilical cord blood transplant patients where the presence of CMV disease was among factors that adversely affected the survival rates of all patients [34]. …”
Section: Discussionsupporting
confidence: 87%
“…A multicenter analysis of 236 children who underwent UCBT in Korea suggested that UCBT was a reasonable alternative as an HSC source9).…”
Section: Discussionmentioning
confidence: 99%
“…11,12 Because high viral loads have been shown to be strong predictors for the development of CMV disease, 13,14 UCBT recipients may also be at increased risk for the development of viral invasion. Incidence rates of CMV in UCBT vary, with reported rates of reactivation fluctuating from 21% to 100% [15][16][17] and CMV disease between 6% and 21%, [17][18][19][20] but different prevention methods and the inclusion of low-risk seronegative recipients limit comparisons.…”
Section: Introductionmentioning
confidence: 99%